Effect of Clinical Teaching Partner Model (CTP) on Nursing Students\' Clinical Training Outcomes - Z Rahnavard; S Ahmadnejad; A Mehran (Tehran University of Medical Sciences, 2009)
Background & Aim: The Clinical Teaching Partner model (CTP) integrates theoretical knowledge with professional skills and brings the reality to workplaces. Closing educational and practical aspects in nursing discipline has been a challenging goal for nursing which requires cooperation between faculty instructors with nurse practitioners such collaboration will led to development and promotion of nursing discipline. Therefore selecting an effective and efficient approach in order to integrate theoretical knowledge with practical experiences would be crucial for nursing profession. This study was conducted in order to investigate the effect of CTP on nursing students;apos clinical skills outcome. Methods & Materials: A quasi experimental, only post test design was applied. Study sample consisted of 1) three faculty instructors, 2) seven registered nurse practitioners who were staff nurses in three pediatric wards and voluntarily participated in the study and 3) fifty two nursing students which were in the 5th semester of nursing BSc. program and had eligible criteria to enter the study. Students were allocated randomly to the intervention (n=28) and control (n=24) groups. Participants in the control group, initially started their internship period in 3 pediatric wards and were evaluated by faculty instructors regarding their clinical skills at the end students in the intervention group, then started their clinical training course in the same ward as control group, but their clinical education was conducted by the nurse practitioners who voluntarily participated in the study and trained initially in the nursing faculties;apos skill lab. Students;apos clinical skills were evaluated by nursing mentors via some instruments at the end of the educational period in addition, clinical education outcomes and nursing students;apos satisfaction of achievement to apprenticeship goals were assessed at the end of the training period. Data were analyzed using the statistical tests including Chi square, Fisher exact test, Mann-Whiney U, and t-test in SPSS. Results: Considering students demographic characteristics, both groups were homogenous. There was a significant difference in the students;apos clinical skills between two groups (P<0.001). A significant difference was shown in the nursing mentors and faculty instructors;apos satisfaction of application of cooperative education method between both groups (P=0.004). No significant differences were found between students;apos satisfaction of reaching to educational outcomes between both groups (P=0.058). There were also no statistical differences between nursing mentors and faculty instructors;apos satisfaction of achieving to clinical education outcomes (P=0.109). Conclusion: According to this study, CTP is an effective approach in clinical education and development of clinical skills for nursing students therefore, application of this method is recommended in clinical nursing education.